ChemInform Abstract: Base‐Mediated Cascade Rearrangements of Aryl‐Substituted Diallyl Ethers. Issue 27 (18th June 2015) - Reid, Jolene P.; McAdam, Catherine A.; Johnston, Adam J. S.; Grayson, Matthew N.; Goodman, Jonathan M.; Cook, Matthew J.
Abstract Selective Wittig‐oxy‐Cope and isomerization‐Claisen rearrangements of diallylethers are investigated.